The materiality of the legal order / Marco Goldoni. - Goldoni, Marco (Cambridge elements. Elements in philosophy of law, 2022)
This Element aims to explore how the relation between societal organisation and legal orders - the question of materiality - has been investigated in philosophy of law. The starting point of the Element is that such relation has often been left invisible or thematised in poor and reductive terms. After having explained the main reasons behind this neglect, the Element provides an overview of the three main approaches to legal philosophy whose contributions, though not always effective, can still provide some insights for a contemporary analysis of legal orders' materiality: materialism, legal institutionalism, and the new materialism. The last section of the Element suggests looking for a footing for the study of materiality in two fields: the metaphysics of relations and the political economy of legal orders.